2015
DOI: 10.12720/joams.3.2.109-122
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Self-Efficacy, Transformational Leadership and Leader Effectiveness

Abstract: Abstract-The aim of this research is to empirically investigate the relationship between a leader's self-efficacy, transformational leadership and leader effectiveness. On the basis of the literature and current leadership research review, the theoretical model, in which transformational leadership mediates the relationship between a leader's selfefficacy and effectiveness, is proposed. The research was conducted within a three-month-long management simulation game at two Czech universities. A total of 32 lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 64 publications
(101 reference statements)
1
13
0
1
Order By: Relevance
“…Still, the degree to which managers can develop behavioral complexity is linked to more effective leadership and higher firm performance. Furthermore, leadership effectiveness is associated with leader intelligence and leader self-awareness (Mesterova et al, 2015;Butler et al, 2014). It might be predicted by leader prototypicality (particularly when followers are exposed to a state of role ambiguity) (Cicero et al, 2010).…”
Section: Behavioral Repertoirementioning
confidence: 99%
“…Still, the degree to which managers can develop behavioral complexity is linked to more effective leadership and higher firm performance. Furthermore, leadership effectiveness is associated with leader intelligence and leader self-awareness (Mesterova et al, 2015;Butler et al, 2014). It might be predicted by leader prototypicality (particularly when followers are exposed to a state of role ambiguity) (Cicero et al, 2010).…”
Section: Behavioral Repertoirementioning
confidence: 99%
“…Based on this assertion, it can be assumed that research has established the connection between self-efficacy and school leadership (Mesterova, Prochazka, &Vaculik, 2015;McCormick, Tanguma, & Lopez-Forment, 2002). McCormick et al (2002) found causal influence of self-efficacy on work performance in general and suggested extending self-efficacy to leadership studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…McCormick et al (2002) found causal influence of self-efficacy on work performance in general and suggested extending self-efficacy to leadership studies. Mesterova et al (2015) research suggests that effective leaders are set apart by what is likely their high levels of self-efficacy or belief in their capacity to perform the job, or task;…”
Section: Literature Reviewmentioning
confidence: 99%
“…A leader's belief in his or her ability to perform across variety of situations plays an important role in his or her effectiveness. Mosterova, J., Prochazka, J., Vaculik, M. and Smutny, P. (2015) state that there're many leaders in management or in political arena who are particularly successful in the leadership roles. They argue that the important contributor to their success might be their beliefs in their capacity to perform a job or particular task, in other words, their self-efficacy.…”
Section: Self-efficacy and Leadershipmentioning
confidence: 99%